ANALYSIS OF CONSUMER BEHAVIOR ON PURCHASE INTENTION OF COUNTERFEIT SHOES IN MANADO - Angkouw, Piere John Paulus; Rumokoy, Farlane S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
The objective of this study is to understand the influence of attitude, value consciousness, social status, perceived price, and past experience toward consumer purchase intention of counterfeit shoes in Manado. The data was collected from 100 respondents that purchase counterfeit shoes and multiple regression analysis was used to test the relationship among variables. The result indicated that the perceived price has significant influence toward consumer purchase intention of counterfeit shoes in Manado. The characteristic of perceived price has substantial positive influence to the consumer purchase intention. The author recommends to shoes producers to pay more attention of the reasons why consumers in Manado consider the price is the main factor that influence the purchasing intention of consumers. Keywords: counterfeiting, counterfeit shoes, consumer behavior, consumer purchase intention